2003
DOI: 10.1590/s0102-35862003000400003
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire of quality of life in patients with primary hyperhidrosis

Abstract: BACKGROUND: Hyperhidrosis or excessive sudoresis is a chronic disease associated with important subjective distress. OBJECTIVE: To propose a specific questionnaire to evaluate the quality of life of patients with hyperhidrosis. METHODS: From October 1995 to March 2002, 378 patients (234 females), with a mean age of 26.8 years, were evaluated before and after video-assisted thoracic sympathectomy. RESULTS: Therapeutic success was obtained in 90% of the procedures. The recurrence rate was 10% for palmar and 11% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
21

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 5 publications
0
30
0
21
Order By: Relevance
“…When it´s used the Campos et al 17 questionnaire 17 , interviewees reported significant harm to QoL in situations of greeting people with handshakes, writing, wearing socks and dancing socially. The data found were similar to those of other studies, which demonstrated intense discomfort and low selfesteem in patients with PH, besides a negative impact on QoL in social and professional settings 7,35,38,39,40,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…When it´s used the Campos et al 17 questionnaire 17 , interviewees reported significant harm to QoL in situations of greeting people with handshakes, writing, wearing socks and dancing socially. The data found were similar to those of other studies, which demonstrated intense discomfort and low selfesteem in patients with PH, besides a negative impact on QoL in social and professional settings 7,35,38,39,40,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com a fórmula, a amostra mínima calculada foi de 232 acadêmicos e a estudada totalizou 300 acadêmicos, selecionados de forma aleatória e sistemática pelo programa estatístico BioEstat 5.0, de maneira a garantir uma amostra homogênea. A pesquisa foi realizada de acordo com as diretrizes e normas regulamentadoras de pesquisa com seres humanos e atende à Resolução nº 466, de 4 . Esse instrumento avalia 20 atividades sobre quatro domínios: funcional-social, pessoal, emocional e condições especiais.…”
Section: Metodologiaunclassified
“…A HP pode manifestar-se isoladamente nos sítios craniofacial, axilar, palmar e plantar, no dorso e na face interna das coxas. Pode haver associações entre os sítios ou concomitantemente nessas regiões 4,5 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…En el caso de la hiperhidrosis axilar, múltiples estudios han evaluado la calidad de vida de los pacientes para medir el impacto de diferentes opciones terapéuticas 19,20 .…”
Section: Escalas De Evaluaciónunclassified